Predictive Value of KDM5C Alterations for Immune Checkpoint Inhibitors Treatment Outcomes in Patients With Cancer - Chen, Xiao-Juan; Ren, Ai-Qun; Zheng, Liang; Zheng, En-Dian (Frontiers in Immunology, 2021)
Lysine (K)-specific demethylase 5C (KDM5C) plays a significant role in the tumor cell proliferation, invasion, drug resistance and the regulation of tumor-related gene expression. Here, we aimed to investigate its predictive value in patients with cancers received immune checkpoint inhibitors (ICIs). We explored the predictive value of KDM5C alterations and the association between KDM5C alteration and immune landscape by using published cohort with clinical outcome and sequenced data from online database. The frequency of KDM5C alterations was 2.1% across 48045 tumor samples with different cancers from 185 studies. KDM5C alterations were correlated with markedly inferior overall survival (OS, 53 vs. 102 months, P<0.0001) than those without. However, in ICI-treated group, patients with KDM5C alterations had a substantially prolonged OS than the wild-type group (not reached vs. 18 months, P=0.0041). The predictive value of KDM5C alterations for ICI treatment outcome was not observed in patients with microsatellite-stable tumors (P=0.2875). Intriguingly, patients with non-small-cell lung cancer and KDM5C alterations receiving ICI had the better progression-free survival than wild type group (13.2 vs. 3.2 months, P=0.0762). Mechanistically, KDM5C altered tumors had dramatically higher TMB level and was associated with significantly higher level of CD8+ T cell infiltration and T effector signature. In conclusion, KDM5C alterations was correlated with enhanced tumor immunogenicity and inflamed anti-tumor immunity, thus resulting in better treatment outcome in cancer patients receiving ICIs.